Voices of the Costa Rican scientific diaspora: Policy lessons from a decade of experiences from our scientists abroad - Jarquin-Solis, Maria Esteli; Lin-Shiao, Enrique; Guerra, Melania; Calderón Zúñiga, Karlissa; Mora Solórzano, Dayana; Gutiérrez, José María (Frontiers in Research Metrics and Analytics, 2022)
TicoTal is an online database and network of Costa Rican scientists studying and working abroad, which was created by the Costa Rican National Academy of Sciences (ANC) in 2010. The main goal of TicoTal is to track the professional development of this scattered pool of talent and open channels for the country to connect with them, as well as among themselves. The platform hosts virtual and in-person seminars and promotes collaborations between Costa Rican scientists with their country and abroad. Since 2012, the monthly TicoTal newsletter has published an in-depth interview with a network member, posing eight recurrent questions about their career pathways, experiences, and challenges abroad, their professional ties to the home country, and potential interest in returning to Costa Rica. This paper analyzes 10 years of diaspora perspectives as reflected by those interviews. We extracted insights about the most common mechanisms and funding sources used by Costa Rican scientists seeking professional opportunities overseas, their level of engagement and collaboration with Costa Rican research and higher education institutions, and the possible incentives that the country could prioritize in order to harness their scientific talent and increase scientific capacities at home. Results from this analysis can inform national policies and investment strategies in R&D infrastructure and resources, by providing a roadmap to engage with the scientific diaspora and benefit from their training and talent, as well as guide future scholarship and exchange programs.